2007
DOI: 10.1262/jrd.18103
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of GABA on Embryonic Gonadotropin-Releasing Hormone Neurons in Rat Hypothalamic Primary Culture

Abstract: Abstract. Gonadotropin-releasing hormone (GnRH) neurons arise in the olfactory placode, migrate into the preoptic area (POA), and then extend axons to the median eminence during embryogenesis. Little information is available concerning the properties of GnRH neurons during the late gestational period when GnRH neurons reach the POA and form neuronal networks, although many studies have examined such properties during earlier developmental stages or the postnatal period. The present study was performed to eluci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Interestingly, increases of GnRH levels were detected in the cortex when migration of GnRH neurons toward their natural location was impaired, as in mice overexpressing GAD-67 in GnRH neurons (43) or in netrin 1 knockout mice (81). GABA B Rs are expressed in GnRH neurons early in development; they were demonstrated in several immortalized GnRH neuron cell lines (30,63,91), in green fluorescence protein-expressing embryonic GnRH neurons (26), and in in situ hypothalamic neurons (86). Intriguingly, GABA B Rs were recently shown to control cell migration and cell positioning within the ventromedial nucleus of the hypothalamus (64) and in the POA-AH (99) in mice.…”
Section: Gnrh Content and Mrna Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, increases of GnRH levels were detected in the cortex when migration of GnRH neurons toward their natural location was impaired, as in mice overexpressing GAD-67 in GnRH neurons (43) or in netrin 1 knockout mice (81). GABA B Rs are expressed in GnRH neurons early in development; they were demonstrated in several immortalized GnRH neuron cell lines (30,63,91), in green fluorescence protein-expressing embryonic GnRH neurons (26), and in in situ hypothalamic neurons (86). Intriguingly, GABA B Rs were recently shown to control cell migration and cell positioning within the ventromedial nucleus of the hypothalamus (64) and in the POA-AH (99) in mice.…”
Section: Gnrh Content and Mrna Expressionmentioning
confidence: 99%
“…Regulation of the gonadotropin axis is provided by both stimulatory and inhibitory inputs conveyed by neurotransmitters, neurohormones, and peripheral peptide and steroid hormones. Among the neurotransmitters involved in this regulation, GABA has been proposed to be of prime importance (16,26,43,65). GABA can regulate the hypothalamic-pituitary-gonadal axis by acting at ionotropic GABA A/C and/or metabotropic GABA B receptors (GABA B Rs).…”
mentioning
confidence: 99%
“…GABA A R stimulation also modulates Gnrh1 mRNA expression in a species-, age-, and model-specific manner [9, 10]. Despite this, knockdown of GABA A Rs in GnRH neurons has minimal effects on fertility [11].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, pharmacological reports suggested that GABA B Rs do not participate in this event [4, 22]. However, because GABA B Rs: a) are present in migrating GnRH neurons [10, 22], b) participate in neuron migration and differentiation [23, 24], c) are present in neural progenitors and in embryonic stem cells [25, 26], and d) participate in E 2 -induced sexual differentiation of several hypothalamic nuclei [27, 28], their participation on GnRH neuron migration and subsequent Gnrh1 expression warrants further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Primary cultures of GnRH neurons have also obtained by dispersion of fetal olfactory tissue derived from of GFP-GnRH mice [48,49]. The presence of GnRH neurons expressing GFP in tissue explant or mixed cell cultures allows to identify living GnRH neurons in tissue slice preparations before and during the experiments; this offers significant experimental advantages for biochemical or electrophysiological experiments [50,51].…”
Section: Citationmentioning
confidence: 99%